Change of direction and change of direction deficit in Danish elite female and male soccer players performing 505 and arrowhead tests - Franch, J.; Koefoed, N. S. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: In soccer, the ability to `cut` and change direction during running is considered an important factor and occurs frequently during a game (1). The basic ability of players to change direction (without ball possession) is often evaluated through sprint running involving one or multiple changes of direction (COD) tests with time as an outcome (CODt), i.e. the 505t or the arrowhead test (AHt). A recent approach to this is to eliminate the linear sprint by calculating the change of direction deficit (CODd) in the 505 (505CODd) (2). The present study investigates this approach in elite Danish female soccer players. The same approach of using CODd in combination with AHt (AHCODd) is investigated in elite Danish male soccer players. METHODS: Two groups participated, with one group being further divided in three age-groups. The groups consisted of 21 top-level female players (EW; age: 19.6±4.9 years, height: 171.6±7.3 cm, bodyweight: 61.8±6.1 kg) and 48 elite male players (EM). The EM group contained players at different age groups; under-17 (EM17; n=17, age: 15.5±0.5 years, height: 180.5±6.7 cm, bodyweight: 70.4±7.9 kg), Under-19 (EM19; n=14, age: 17.2±0.7 years, height: 181.0±7.9 cm, bodyweight: 68.8±7.76 kg) and senior (EMS; n=17, age: 23.5±4.17 years, height: 183.5±6.0 cm, bodyweight: 78.6±5.7 kg). All groups performed a 30 m sprint test, with EW also recording a 10 m split time. Additionally, EW performed the 505t and 505CODd. The male players performed the AHt and the AHCODd. For CODd calculations 10m and 30m linear sprint time was subtracted from 505t and AHt, respectively. Split and final times were recorded using infrared photocells. Witty (Microgate, Bolzano, Italy and Ci; Brower Timing, Draper, UT, USA, for EM and EW respectively). All time comparisons were performed using one way ANOVA. Correlation between CODt and CODd was performed with `Pearson`s r correlation` or `Spearman Signed Rank Test` and all male players were pooled for correlation analysis. RESULTS: Across groups EMS was significantly faster in the 30 m sprint compared to EM19 and EM17 and EW was significantly slower than all other groups (p < 0.05). For EW, positive correlation was found for 10 m sprint and 505t (r = 0.67), and an insignificantly negative relationship between 10 m sprint and 505CODd. For EM 30 m sprint and AHt correlated (r = 0.68), and an insignificantly negative relationship between 30 m sprint and 505CODd. CONCLUSION: In Danish elite soccer players, the present study shows high correlations between CODt and linear sprint times, in both male and female players, indicating that linear sprint ability, and not COD is evaluated in the COD tests used. The results therefore support similar results in experienced cricketers (2) however, the observed insignificant negative relationship between linear sprint time and CODd needs further research on order to qualify player performance.